PENGETAHUAN DAN SIKAP REMAJA PUTRI TERHADAP KEJADIAN ANEMIA - Ridatillah, Wenny Mai; Tunggal, Tri; Dewi, Vonny Khresna; Hapisah, Hapisah (Jurnal Keperawatan dan Kesehatan, 2026)
Background: Adolescent girls are one of the groups at high risk of experiencing anemia. Data from MTsN 5 Hulu Sungai Utara school shows that 31.5% of adolescent girls experience anemia. Lack of knowledge and attitudes make adolescents more susceptible to anemia. Knowledge and attitudes of adolescent girls about anemia will influence behavior in preventing anemia. Objective: To find out the correlations between knowledge and attitudes of adolescent girls towards the incidence of anemia at MTsN 5 HSU. Method: The design of this study is observational analytic with a cross-sectional approach. The sampling technique used total sampling with a sample size of 56 people. The instruments used were questionnaire sheets and blood tests. Data analysis used the Chi-Square test. Result: There were 20 (35.7%) female adolescents who experienced anemia. The knowledge of female adolescents in the good and sufficient category was 26 (46.4%). There are 27 teenagers (48.2%) who have negative attitudes. There was a correlations between knowledge (P = 0.018) and attitude (P = 0.015) of female adolescents with the incidence of anemia at MTsN 5 HSU. Conslusion: Knowledge and attitudes of adolescent girls towards the incidence of anemia at MTsN 5 HSU. Adolescent girls should continue to actively seek information about the incidence of anemia to increase their knowledge and prevent anemia.